(3GdEWGQ GdJfXjej hGdJYGbOj ddJLGQI GdEdcJQhfjI (B: s (3OQGSI JMdjdjI ddeTcdGJ hGdMdhd GdebJQMI (B/ s - (3ejfG YGOd GScfOQ s; (3SejMI eUWaj GdbdjhHj (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B-(3LGeYI GdbGgQI,s, 2014)
(3JJfGhd gPg GdOQGSI ehVhY GdEWGQ GdJfXjej hGdJYGbOj ddJLGQI GdEdcJQhfjI; hgj JfbSe Edi aUd JegjOj jHjf eGgjI GdJLGQI GdEdcJQhfjI ef MjK GdJWhQ, hGdNUGFU, hGdCTcGd, hGdeRGjG hGdYjhH, Ke jCJj GdHGH GdChd GdPj jJfGhd GdWHjYI GdbGfhfjI ddYdGbI GdJYGbOjI GdEdcJQhfjI hCWQGagG hNUGFUgG, hCNjQG GdHGH GdKGfj GdPj jJfGhd GdeYhbGJ hGdJMOjGJ GdYedjI hGdbGfhfjI ddJLGQI GdEdcJQhfjI(B.s
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B2014.s
(3HHdjhLQGajG(B: (3UaMGJ(B259-365.s
Keywords: (3NUGFU GdJLGQI GdEdcJQhfjIs; (3GTcGd GdJLGQI GdEdcJQhfjIs; (3CfhGY GdJLGQI GdEdcJQhfjIs; (3GdYbO GdEdcJQhfjs; (3hSjW EdcJQhfjs; (3GdCehGd GdJLGQjI GdEdcJQhfjIs; (3GdChQGb GdJLGQjI GdEdcJQhfjIs; (3GdJhbjY GdEdcJQhfjs; (3GdJhajb GdEdcJQhfjs; (3GdJMcje GdEdcJQhfjs; (3GdeYGedGJ GdVQjHjI GdEdcJQhfjIs; B2B; B2C; C2C; (3NUGFU GdJLGQI GdEdcJQhfjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- 2014